Airway immune responses to COVID-19 vaccination in COPD patients and healthy subjects. Issue 2 (25th August 2022) - Southworth, Thomas; Jackson, Natalie; Singh, Dave
COPD patients have a higher risk of developing severe illness and mortality following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection [1]. Vaccination protects against coronavirus disease 2019 (COVID-19) through the development of systemic and airway immune responses. Patients with COPD display altered humoral immunity, with reduced antibody responses compared to healthy controls [2, 3]. We studied SARS-CoV-2 vaccine-specific immune responses in COPD patients versus healthy controls, using systemic, nasal and sputum samples. Airway and blood immune responses to COVID-19 vaccination were examined in COPD patients and healthy subjects. Anti-spike IgG, but not IgA, levels were higher in airways post-vaccination, with similar responses in COPD patients and healthy subjects. https://bit.ly/3zt6D6v